Estimation of Critical Properties of Eucalyptol, Alpha-Terpineol, Limonene, and Caryophyllene in Eucalyptus Oil (Melaleuca leucadendra) Using the Group Contribution Method - Prasetyo, Muhammad Dewa; Muljani, Srie; Sari, Amilia Putri Puspita (Jurnal Rekayasa Kimia & Lingkungan, 2025)
Critical property estimation of compounds in eucalyptus oil has been conducted using the Group Contribution method to improve the accuracy of calculations of critical temperature (Tc), critical volume (Vc), critical pressure (Pc), and normal boiling point (Tb). This study updates the previous research by adding a comparative analysis of estimation errors between methods. Eucalyptus oil was extracted using microwave hydrodistillation followed by vacuum distillation to determine experimental data, then estimated using the Joback, Constantinou-Gani (CG), Wilson-Japerson (WJ), and Marrero-Pardillo (MP) methods. The results show that the Wilson-Japerson method provides the most accurate Pc estimation with %AAE of 12.7819%, the Marrero-Pardillo method is best for Vc with %AAE of 5.3393%, the Marrero-Pardillo method provides the most accurate Tc estimation with %AAE of 2.7143%. The Joback method is most suitable for Tb with a %AAE of 20.0828%. The application of the results of this study in the essential oil industry is crucial in optimizing the extraction and distillation process, increasing the efficiency of separation units, developing refining technology, and formulating essential oil-based products. The method with the best accuracy can be used in the design of distillation equipment and thermodynamic reactors, thereby improving production efficiency and product quality in the pharmaceutical, cosmetic, and natural chemical industries.